Identification and Prioritization of Solutions for Restoring Investors' Confidence in the Capital Market of the Islamic Republic of Iran - Yaser Sharifi; Mohammad Tohidi; Meisam Hamedi (Journal of Asset Management and Financing)
The loss of investor confidence in financial markets can result in liquidity outflows and market collapse. Restoring investor trust requires identifying the factors that have eroded trust. This research aimed to identify the factors influencing the decline of the Tehran Exchange Price Index (TEPIX) in 2019 and the subsequent loss of investor confidence. Furthermore, it aimed to extract and prioritize solutions to restore investor confidence. Expert interviews were conducted to collect data, which were then analyzed using thematic analysis. Friedman's non-parametric test was utilized to prioritize the solutions. The study identified 26 significant factors contributing to the decline of the stock market and the loss of investor confidence. These factors were categorized into 4 groups: macroeconomic governance, capital market, macroeconomics, and media. Additionally, 27 solutions to restore investor confidence were identified within the same four categories. According to the experts’ opinions, the most crucial solutions included preventing government intervention and non-expert comments by government officials in the capital market, reforming the economic system to enhance economic stability, increasing transparency in information and decision-making processes, and improving the performance of the Securities and Exchange Organization of Iran in detecting and addressing violations.